Assessment of chemical, ultrasonic, diode laser, and Er:YAG laser application on debonding of ceramic brackets - Ahmed S. Khalil; Nazla M. Tamish; Ahmed R. Elkalza (BMC, 2022)
Abstract Background Risk of enamel damage that often accompanies ceramic brackets debonding raises the demand of finding an optimal method for debonding of them without adverse effects. Different techniques were proposed in an attempt to facilitate their debonding. Comparison of these techniques is crucial. The aim of this study was to evaluate and compare different techniques for debonding of ceramic brackets in terms of shear bond strength and adhesive remnant index. Materials and methods A total of 100 extracted premolars were randomly allocated into 5 groups. Ceramic brackets were then bonded to teeth using light cure composite resin. Among test groups; group I: served as control, group II: chemical aided debonding via peppermint oil, group III: ultrasonic aided debonding, group IV: diode laser aided debonding, and group V: Er:YAG laser aided debonding. Brackets were shear tested using universal testing machine followed by ARI assessment and evaluation of enamel microstructure was performed using scanning electron microscopy. Results A significantly lower shear bond strength was found in ultrasonic, diode, and Er:YAG laser groups. However, no significant difference was found in the chemical group. A significantly higher adhesive remnant index was found solely in Er:YAG laser group with minimal enamel microstructure alterations. Conclusions Er:YAG laser is a promising tool in debonding ceramic brackets. Ultrasonic and diode laser significantly reduced shear bond strength. Yet, adhesive remnant index in both groups revealed no difference. Chemical aided debonding had little effect and hence, it cannot be recommended without further development.